THE NEEDS OF DEVELOPING PRIMARY SCHOOL ACADEMIC MANAGEMENT BASED ON THE CONCEPT OF FUTURE LEADERSHIP SKILLS: ความต้องการจำเป็นในการพัฒนาการบริหารวิชาการโรงเรียนประถมศึกษา ตามแนวคิดทักษะภาวะผู้นำในอนาคต - Sonprasit, Jinda; Siribanpitak, Pruet; Xupravati, Penvara (Journal of Education and Innovation, 2023)
The purpose of this research was to study the current and desirable condition of primary school academic management and to analyze the priority needs of developing primary school academic management based on the concept of future leadership skills. This research applied a quantitative approach. The population were primary schools under the office of the basic education commission, total of 27,414 schools. The sample were 394 primary schools, selected by applying stratified random sampling, and simple random sampling. The key respondents were 1,970 people including 788 school administrators and 1,182 teachers. The research instrument was a questionnaire. The data were analyzed by frequency, percentage, means, standard deviation, and PNImodified. The research result was as follows 1) the current condition of primary school academic management based on the concept of future leadership skills; overall at a high level, classified with regards to academic management, it was found that the highest average was the development of teaching and learning, followed by the development of measurement and evaluation and the development of the school curriculum, respectively. When classified by future leadership skills, it was found that the highest average were interpersonal communication skills, followed by self-confidence skills, and adaptive skills, respectively. The desirable; overall at a highest level, classified with regards to academic management, it was found that the highest average was the development of measurement and evaluation, followed by the development of the school curriculum, and the development of teaching and learning, respectively. When classified by future leadership skills, It was found that the skills with the highest average were interpersonal communication skills, followed by inspiring skills, and innovation skills based on morality and ethics, respectively 2) The priority needs of developing primary school academic management based on the future leadership skills classified with regards to academic management; overall, the highest priority needs index fell on the development of measurement and evaluation (PNImodified = 0.127), the development of the school curriculum (PNImodified = 0.117) and the development of teaching and learning (PNImodified = 0.085), respectively. When classified with the future leadership skills; overall, the highest priority needs index fell on the critical thinking skills (PNImodified = 0.140), the strategic planning skills (PNImodified = 0.137) and the creative problem-solving skills (PNImodified = 0.116), respectively.